2017
DOI: 10.3102/0002831217714321
|View full text |Cite
|
Sign up to set email alerts
|

Pathways to Educational Success Among Refugees: Connecting Locally and Globally Situated Resources

Abstract: Biographical SketchesSarah Dryden-Peterson is an Associate Professor of Education at the Harvard Graduate School of Education. Her research focuses on education in armed conflict and the ways in which learning, pedagogies, and relationships may alter trajectories of conflict for nation-states and individuals.Negin Dahya is an Assistant Professor at the Information School at the University of Washington. Her research explores how social and cultural contexts shape digital media production, social media particip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
38
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 113 publications
(40 citation statements)
references
References 44 publications
2
38
0
Order By: Relevance
“…In addition to formal learning, research into virtual support networks in camp settings, showed the great importance of such community building for easing pathways into higher education and to facilitate study success, especially for female learners (Dahya and Dryden-Peterson 2017;Dryden-Peterson, Dahya, and Adelman 2017). Furthermore, technology helps to keep educational pathways mobile, e.g., studying does not need to stop when people move (GIZ 2016, 5).…”
Section: Online Education For Refugeesmentioning
confidence: 99%
“…In addition to formal learning, research into virtual support networks in camp settings, showed the great importance of such community building for easing pathways into higher education and to facilitate study success, especially for female learners (Dahya and Dryden-Peterson 2017;Dryden-Peterson, Dahya, and Adelman 2017). Furthermore, technology helps to keep educational pathways mobile, e.g., studying does not need to stop when people move (GIZ 2016, 5).…”
Section: Online Education For Refugeesmentioning
confidence: 99%
“…Moodle, Blackboard, Canvas) or alternative digital tools such as email or file sharing over mobile phones and tablets. Text and instant messaging are notable aspects of these educational landscapes Dryden-Peterson, Dahya & Adelman, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…In this landscape, digital communities may be an asset to teachers and their students to support teacher training, provide digital content, and enhance opportunities for literacy and learning (see Unwin, Weber, Brugha & Hollow, 2017). Our own previous work has identified a crucial, supportive role that both mobile phones and social networks have in the education of refugees in Kenya, particularly among secondary school graduates who often proceed to become teachers in the camps (see Dryden-Peterson et al, 2017). We drew on data collected through in-depth interviews with refugees from Dadaab Refugee Camps pursuing postsecondary education and on survey data from the Somali diaspora to understand the role of transnational networks, including information and communication technology (ICT) and social media.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations